Renewable Energy Utilizing for Clean Energy Development - Setiartiti, Lilies (International Journal of Energy Economics and Policy, 2018)
Yogyakarta is one of the provinces in Indonesia that has no fossil energy potential. All economic activities is highly depend on the stability of energy supplies from other regions. Due to the limited energy resources so that energy efficiency becomes very important. This research was conducted to predict the effects of different development alternatives on future energy consumption and carbon emission as a clean energy indicator. Energy demand modeled by sector using intensity approach, that is calculate the amount of energy used per unit of activity. Applying long range energy alternative planning model was built to analyze the future trends of energy demand, energy structure and carbon emission from the base year 2012 to 2030 under different scenario composition that is business as usual (BAU), moderate (MOD), and optimistic (OPT) scenario. The results show that energy demand grew an average of 7.63% per year. Transportation sector is the largest energy user with a percentage of over 60% of overall energy demand, as well as the largest contributor to carbon emissions. Total energy demand in Yogyakarta under MOD and OPT scenarios is expected to reach 195.878,1 thousand BOE, and 184.695,1 thousand BOE, lower than those of the BAU scenario, respectively. Based on the MOD and OPT scenario, greenhouse gases (GHG) emissions in 2030 respectively amounted to 6.03 million tons of CO2 equivalents and 5.75 million tons of CO2 equivalents. With the implementation of programs that can support the OPT scenario, GHG emissions can be reduced to 12.5% when compared to the GHG emissions generated by the BAU. Overall, this research provides some important insights for Yogyakarta in terms of future energy conservation and highlights possible steps for policy makers to develop a sustainable clean-energy region. Keywords: Yogyakarta, Carbon Emission, Energy Demand, Long Range Energy Alternative Planning Model JEL Classifications: Q2, Q3, Q4, Q5